The 'phantom mask' in Phoenix (2014) and See You Up There (2017). Issue 5 (20th October 2022) - Zhao, Siyuan
Abstract : This paper applies a theoretical approach to discuss the ways in which film as a mode of narration uses the perception of the 'phantom mask' as an emblem of post-war trauma. By associating the mask with trauma and memory in the context of two post-war films, Phoenix (2014) and See You Up There (2017), it analyses how individual trauma is presented and interwoven with a historical event. Firstly, the paper coins a new term 'phantom mask', and explains how this is derived from the phenomenon of the 'disfigured face' associated with 'shell shock' and other features in theories of trauma outlined by scholars. Secondly, as the characters in these films are trapped at a certain point in their past, I argue that a space for role-playing is created that allows the narration of individual traumatic experience to deviate from collective trauma, thereby distinguishing it from most post-war traumatic films. Thirdly, I suggest that this schizophrenia-like narrative allows a character to abandon their personal responsibility for the grand historical narrative in a kind of 'a guilt-free homecoming'. Using this framework, the paper strives to provide a critical strategy and method for analysing literary trauma, refocusing on the possible ways in which history is constructed by both trauma and memory.